NARASI VISUAL CERITA FABEL DALAM KARYA SENI LUKIS - Ariesa Pandanwangi; Belinda Sukapura Dewi; Shopia Himatul Alya (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
Bandung is one of the creative cities in Java, especially West Java. Proven Bandung has a lot of local wisdom dug up from legendary stories, animal fable stories, culinary riches, and many more which later became interesting ideas into the concept of creating art. This local wealth is an important claim by artists who actively work. This research will reveal the expression of artists in paintings. They express their expression by bringing up the fable story of the archipelago. Archipelago fable story is processed, dug up and used as a source of inspiration to create works of art. The problems in this study are (1) What is the concept of a painting that was conceived from the fable story of the archipelago. (2) What is the visualization of the archipelago fable painting created by female artists ?. This research method is descriptive qualitative by examining the aesthetic aspects which include elements of the object, composition, color, harmonization. The media used in this painting is fabric. Samples of paintings, taken from works created by women from an exhibition held in Bandung. The coloring process with the colet technique. The color used is the dye for the fabric. The findings in the research are the concept of the work carried by artists visualizing animal stories that can be used as good moral examples. This exhibition is important because in addition to visual narration there is also a message delivered to the public. Whereas visually, many female artists use realistic objects, center composition, contrasting and attractive colors. The results of this study the concept of fable stories are brought back into an attractive visual narrative with colors that are presented in contrast with many techniques in coloring.